Strategies to Increase Employee Work Motivation Through Incentives and Operational Services: Strategi Untuk Meningkatkan Motivasi Kerja Karyawan Melalui Pemberian Insentif dan Jasa Operasional - Valencia Angel; Sulastri Irbayuni (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Companies need strategies to achieve their goals. Without a strategy, company performance cannot be managed optimally and its goals will not be achieved optimally. Giving rewards plays an important role in the strategy to improve performance because it can increase employee motivation to achieve company goals. The purpose of implementing this internship activity is to increase insight into the world of work, provide soft skill development, for work preparation, provide understanding related to a particular industry or field of work, and find out the strategies used by the company PT Nusantara Medika Utama in increasing employee performance motivation. The method of implementing this program consists of the preparation, implementation, and reporting stages. The program implementation lasted for 4 months at PT Nusantara Medika Utama, starting on February 19 - June 18. The results of the internship activity analysis showed that the ability to analyze employee needs in improving performance was able to improve employee motivation skills. PT Nusantara Medika Utama provides work motivation by providing feedback in the form of incentives and operational services.